2012
DOI: 10.3389/fendo.2012.00050
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Interactions of Thyroid Hormones and Thyroid Stimulation Hormone in the Female Reproductive Tract have an Impact on Female Fertility

Abstract: Thyroid disease often causes menstrual disturbances and infertility problems. Thyroid hormone (TH) acts through its receptors, transcription factors present in most cell types in the body. Thyroid stimulating hormone (TSH) stimulates TH synthesis in the thyroid gland, but seems to have other functions as well in the female reproductive tract. The receptors of both TH and TSH increase in the receptive endometrium, suggesting that they are important for implantation, possible by influencing inflammatory mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…The results were in good agreement with the findings of previous studies [ 5 , 13 ]. The binding of thyroid hormones to the thyroid hormone receptors mediates the biological activities of T3 via transcriptional regulation through transcription factors present in the female reproductive tract [ 50 ]. The relative levels of immunostaining intensity in each treated group were different from those of the control group, which may be because of the changes in thyroid hormones in different thyroid states.…”
Section: Discussionmentioning
confidence: 99%
“…The results were in good agreement with the findings of previous studies [ 5 , 13 ]. The binding of thyroid hormones to the thyroid hormone receptors mediates the biological activities of T3 via transcriptional regulation through transcription factors present in the female reproductive tract [ 50 ]. The relative levels of immunostaining intensity in each treated group were different from those of the control group, which may be because of the changes in thyroid hormones in different thyroid states.…”
Section: Discussionmentioning
confidence: 99%
“…There is an important occurrence of infertility and anovulation in hypothyroid patients [10, 11], which may involve metabolic alterations and inflammation [12, 13]. However, scarce studies have approached the influence of thyroid dysfunction in the ovarian failure.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that G protein-coupled TSHR is widely expressed in the fetomaternal unit (Aghajanova et al, 2011;Stavreus-Evers, 2012), which indicated that this receptor, and probably TSH have important role in embryo implantation. Previously, it was reported that G protein-coupled TSHR is widely expressed in the fetomaternal unit (Aghajanova et al, 2011;Stavreus-Evers, 2012), which indicated that this receptor, and probably TSH have important role in embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study has also revealed that TSHR expression of in the uterus was increased at the day of implantation, under the influence of TH. Previously, it was reported that G protein-coupled TSHR is widely expressed in the fetomaternal unit (Aghajanova et al, 2011;Stavreus-Evers, 2012), which indicated that this receptor, and probably TSH have important role in embryo implantation. The increased in TSHR expression under the influence of TH might indicate enhanced effect of TSH in the endometrium.…”
Section: Discussionmentioning
confidence: 99%